2020
DOI: 10.1002/jcop.22392
|View full text |Cite
|
Sign up to set email alerts
|

Complex assessment of relationship quality within dyads

Abstract: Higher quality relationships have been linked to improved outcomes; however, the measurement of relationship quality often ignores its complexity and the possibility of co‐occurring positivity and negativity across different contexts. The goal of this study is to test the added benefit of including multiple dimensions, contexts, and perspectives of relationship quality from both individuals in predicting marital functioning. The Social Relationships Index assessed positive and negative dimensions of relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Recent research has examined ambivalence in marriage and found those who report spousal ambivalent behavior have worse psychological and physiological health [ 29 , 36 39 ]. The present study’s finding supports this literature, and we echo previous researchers in urging future studies to include multidimensional measures of relationship quality [ 35 , 106 ]. Additionally, our results extend this literature by exploring a unique method by which to assess the speed at which stress buffering occurs: pupillometry.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recent research has examined ambivalence in marriage and found those who report spousal ambivalent behavior have worse psychological and physiological health [ 29 , 36 39 ]. The present study’s finding supports this literature, and we echo previous researchers in urging future studies to include multidimensional measures of relationship quality [ 35 , 106 ]. Additionally, our results extend this literature by exploring a unique method by which to assess the speed at which stress buffering occurs: pupillometry.…”
Section: Discussionsupporting
confidence: 90%
“…Marital quality however is often seen on a unidimensional scale being either supportive (high support, low strain) or aggravating (low support, high strain), yet marriages can contain both high elements of support and high elements of strain concurrently (ambivalence). In a study evaluating 183 couples Reblin, Vaughn, Birmingham et al [35] showed that the inclusion of multiple dimensions of relationship quality improved prediction of marital functioning. Recent research has examined ambivalence in marriage and found those who report spousal ambivalent behavior have worse psychological and physiological health, and worse relationship processes than marriages with supportive behaviors [29,[36][37][38][39].…”
mentioning
confidence: 99%
“…This study describes both broad and specific measures of support in an end-of-life cancer caregiving context over time. Our findings, similar to work in broader relationship contexts [ 25 , 26 ], suggests that adding additional information about more specific aspects of social interactions adds predictive value compared to more general measures of support.…”
Section: Discussionsupporting
confidence: 84%
“…One meta-analysis found that most standard unidimensional measures of marital quality did not adequately distinguish between positive and negative aspects of marital behavior [ 51 ], and may not fully capture the nuances of marital relationships [ 52 ]. Reblin et al [ 53 ] showed that the inclusion of multiple dimensions of relationship quality improved prediction of marital functioning over that of unidimensional scales. Indeed, Birmingham et al [ 39 ] found that despite the positivity in these ambivalent relationships, individuals whose spouses’ or own behavior was ambivalent, did not receive the same cardiovascular protection in the form of lower blood pressure as supportive marriages.…”
Section: Introductionmentioning
confidence: 99%